Implementasi Manajemen Tata Usaha Berbasis Servis Quality Dalam Meningkatkan Efektivitas Pelayanan Administrasi Pendidikan - Huda, Dalfa Muharimatul; Ginanjar, Muhammad Hidayat; Heriyansyah (Program Studi Manajemen Pendidikan Islam Fak. Ilmu Tarbiyah dan Keguruan, 2026)
Educational administrative services constitute one of the strategic elements in supporting the effectiveness of educational implementation in schools. The quality of administrative services is not only determined by the completeness of documents but also by the quality of services as perceived by service users, including teachers, students, and educational staff. This study aims to examine and analyze the implementation of service quality–based administrative management in improving the effectiveness of educational administrative services at SMK Bina Sejahtera-3, Bogor City. This research employs a qualitative approach with a descriptive design. Data were collected through in-depth interviews, observation, and documentation. Research informants were selected using purposive sampling and included the principal, head of administration, administrative staff, Dapodik operator, teachers, and students. Data validity was ensured through source and technique triangulation as well as member checking, while data analysis was conducted using thematic analysis. The results indicate that the implementation of service quality–based administrative management has been fairly effective when viewed through the five dimensions of service quality: tangible, reliability, responsiveness, assurance, and empathy. The tangible dimension is reflected in the availability of adequate and well-planned administrative facilities and infrastructure. The reliability dimension is demonstrated by the accuracy and consistency of administrative data management in accordance with established procedures. The responsiveness dimension is evident in the prompt and appropriate responses of administrative staff in addressing administrative needs. The assurance dimension is realized through the competence and professionalism of administrative personnel, while the empathy dimension is reflected in a friendly attitude, attentiveness, and concern for service users. Overall, the application of service quality–based administrative management contributes positively to improving the effectiveness of educational administrative services at SMK Bina Sejahtera-3, Bogor City.